Durability of Building and Construction Sealants and Adhesives : 6th volume - White, Christopher C.; Miyauchi, Hiroyuki (Journal of American Society for Testing and Materials. Selected technical papers, 2018)
"Contains peer-reviewed papers that were presented at a symposium held June 14-15, 2017, in Toronto, Ontario, Canada. The symposium was sponsored by ASTM International Committee C24 on Building Seals and Sealants and Subcommittee C24.01 on Terminology of BuildingSeals and Sealants."